Determinants of Capital Adequacy Ratio (CAR) 19 Commercial Banks in Indonesia Based on Risk Based Bank Rating - Nuviyanti, Nuviyanti; Anggono, Achmad Herlanto (Journal of Business and Management, 2014)
Bank Indonesia issued some considerations for commercial banks in order to create healthy banking system and have ability to compete with worldwide should be preparing Minimum Capital Adequacy Ratio that meets with the international standards. Capital Adequacy ratio means amount of capital to ensure that banks can handle risk exposures. Implementing the Minimum Capital Adequacy Ratio must be adjusted to risk profile for absorb the potential losses on risk exposure as well as to fulfilling the minimum capital requirement. The objective of this research is to deteminants of capital adequacy ratio based on risk based bank rating 19 commercial bank in Indonesia.The research involved the use of Multiple Regression Linier based on Ordinary Least Square estimation technique to determine the affect of the independent variables - Good Corporate Governance measured by operating expense to operating income ratio and net interest margin, Risk Profile measured by non performing loan ratio and loan to deposit ratio, Earning measured by return on asset ratio and return on equity – Secondary data were obtained from condensed financial statement conventional bank quarterly that derived from Bank Indonesia covering 2008 to 2013. Using significant level of 5%. The result analysis obatained from coefficient corelation (), T test and F test. The research found  that operating expense to operating income ratio, loan to deposit ratio, return on equity ratio have negative significant affect with capital adequacy ratio in the other hand non performing loan ratio and return on asset ratio have positive influence with capital adequacy ratio. While variables that most affecting with dependent  variable is return on asset ratio that has coefficient value of  2.546153. Keywords : Capital Adequacy Ratio, Risk Based Bank Rating, Commercial Bank in Indonesia